Home-School Cultural Value Mismatch: Antecedents and Consequences in a Multi-Ethnic Sample Transitioning to College - Vasquez-Salgado, Yolanda; Greenfield, Patricia M.; Guan, Shu-Sha Angie (Frontiers in Psychology, 2021)
Qualitative work has documented home-school cultural value mismatch – mismatch between collectivistic family obligations and individualistic academic obligations – experienced by Latinx first-generation college students during their first year of study at a four-year university. This study extends prior research by examining home-school cultural value mismatch among a larger, multi-ethnic sample from Latinx, Asian and European American backgrounds (N = 155) in order to quantify the phenomenon and generalize it across multiple ethnic groups. Antecedents and consequences of different forms of mismatch were assessed in separate models. In modeling antecedents, we found that Latinx background, first-generation college status and low parental income were interconnected. However, among these three variables, it was first-generation college status that was the sole predictor of strong collectivistic motives for attending college; these motives were, in turn, associated with more frequent mismatch between family obligation and academic obligation. In addition, being female directly related to mismatch prevalence, as did living close to home. In modeling consequences of cultural value mismatch, frequent home-school cultural value mismatch predicted mental and physical health distress, which predicted academic problems; such problems were, in turn, related to lower grades. Our findings document the generalizability of this experience for first-generation college students from all ethnic backgrounds, as well as the unique experiences of students who identify as female or live close to home. Our findings also reveal the health and academic costs associated with this mismatch. Implications for research, intervention, and institutional change are discussed and have become increasingly important, given recent societal events that require most students to remain closer to home during distance learning.